MATHEMATICAL MODELING OF THE DRYING CURVES OF FOXTAIL MILLET SEEDS IN SPOUTED BED - do Nascimento, L. D.; Corumbá, L. G.; Rocha, S. C. S.; Taranto, O. P.; Costa, C. M. L.; de Faria, L. J. G. (Revista de Engenharia Térmica, 2015)
In order to provide a contribution to future studies of foxtail millet (Setaria italica), the drying kinetics of the seeds was investigated at three different temperatures: 44, 65 and 86°C. The seeds of S. italica with a moisture equal to 30% in dry basis were dried in a conical-cylindrical spouted bed during an interval of 132 min. Some empirical mathematical models were selected to describe the experimental drying kinetics data (Lewis, Henderson and Pabis, Page, Diffusion approach, Midilli and Wang and Singh) and the best models were chosen according to the statistical tests results (coefficient of determination, mean relative percent deviation, mean square root error and residue distribution), using the software Statistica® 7.0 and applying the Quasi-Newton method. Only the decreasing rate period was observed in the drying kinetic curves, indicating that the removal of moisture content was preferably by the diffusion mechanism, which is a characteristic behavior of fibrous products, like the agricultural products. The models of Diffusion Aproach, Page and Midilli were the most suitable to describe the experimental drying curves.